The Influence of Sex and Weather on the Activity Budget of Javan Slow Lorises (Nycticebus javanicus) in Garut Regency, West Java - Helmi Romdhoni; Dyah Perwitasari-Farajallah; Entang Iskandar; Katherine Hedger; Marco Campera; Hélène Birot; K.A.I Nekaris (Journal of Tropical Biodiversity and Biotechnology, 2022)
The Javan slow loris (Nycticebus javanicus) is a nocturnal primate endemic to Java. Previous studies on slow loris activity are limited to general daily activity, and there is a lack of research on the potential sex differences in slow loris activity. This study aims to analyze differences in the daily activity of the Javan slow loris based on sex. From August to December 2018, the daily activity of six wild Javan slow lorises was recorded using behavioral observations with instantaneous point sampling at 5-minute intervals. Differences in male and female slow loris activity were analyzed using the Generalized Linear Mixed Model (GLMM). We set sex and weather as fixed factors and individuals as random effects. The results of this study showed that females spent more time feeding and less time resting than males. In addition, the Javan slow loris behavior was affected by temperature and humidity like other slow loris species.